2020
DOI: 10.3390/antiox9040280
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hydrogen Peroxide and Peroxiredoxins throughout the Cell Cycle

Abstract: Hydrogen peroxide (H2O2) is an oxidizing agent that induces cellular damage at inappropriate concentrations and gives rise to an arrest during cell cycle progression, causing cell death. Recent evidence indicates that H2O2 also acts as a promoter for cell cycle progression by oxidizing specific thiol proteins. The intracellular concentration of H2O2 is regulated tightly, enabling its use as a cellular signaling molecule while minimizing its potential to cause cellular damage. Peroxiredoxins (Prxs) have peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 108 publications
0
27
0
Order By: Relevance
“…Such oxidation can result in structural modification leading to the selective regulation of protein functions (as in phosphatase, kinases, etc.) and can thus have an important impact on regulating signaling pathways in a large range of physiological contexts [277][278][279][280].…”
Section: Role Of Nox In Redox Signalingmentioning
confidence: 99%
“…Such oxidation can result in structural modification leading to the selective regulation of protein functions (as in phosphatase, kinases, etc.) and can thus have an important impact on regulating signaling pathways in a large range of physiological contexts [277][278][279][280].…”
Section: Role Of Nox In Redox Signalingmentioning
confidence: 99%
“…NADPH oxidases (NOX), particularly NOX1 and NOX4 may be the source of H 2 O 2 [ 26 ] and H 2 O 2 generated by NOX in response to growth factors are required to activate the extracellular signal-regulated kinase (ERK) and p38 which increase the expression of cyclin D to promote the transition from G0 to G1 phase. Several key proteins involved in different phases of the cell cycle with redox sensitive residues at their active sites, like Cdc14B, PP1, PP2, Cdc25C, could be the targets [ 27 , 28 ] and it has been proposed that Prdx1, Prdx2 and Prdx3 play important roles to maintain the redox state of those target proteins thus protecting the cell against an undesired progression through the cell cycle [ 29 , 30 ]. More specifically and pertinent to the study reported herein, PRDX6 has been described to activate NOX1 oxidase activity through physical interaction with NOX1 components and through its PLA2 activity [ 31 ] as occurred also with NOX2 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we focused on Prdx3 as a critical player involved in senescence, especially in a MondoA-regulated pathway. Prdx1-6, enzymatic antioxidants with redox signaling, are involved in the proper cell-cycle progression (Heo et al, 2020;Rhee and Kil, 2017). Consistent with this role, there is a report that Prdx3 levels are reduced in intrahepatic cholestasis pregnancy placenta with mitochondrial dysfunction and senescence (Wu et al, 2016).…”
Section: Loss Of Mondoa Disrupts the Regulation Of Prdx3 And Rubiconmentioning
confidence: 86%